Judicial Mechanisms for Medical Disputes: A Normative Analysis of Litigation and Non-Litigation Pathways in Indonesia - Gomes, Florindo Cardoso; Adiyaryani, Ni Nengah (JURNAL AKTA, 2025)
Law Number 17 of 2023 controls how medical services are given in Indonesia. It also explains how to solve medical disputes. These disputes often happen because of mistakes either on purpose or by accident by healthcare workers. Articles 305, 308, and 310 explain how to handle these cases. However, they are not clear and are hard to apply. There are no clear rules about panel decisions, case deadlines, or how to judge if a doctor was negligent. This study uses a legal research method based on laws and legal ideas. It uses primary, secondary, and supporting legal sources through library research and logical analysis. The study finds that the system for solving medical disputes in Indonesia is unclear. This is because of weak law enforcement, poor legal rules, and different ways of reading the law. This creates unfairness for patients, doctors, and health institutions. To solve this, Indonesia needs to build a special medical court. This is important and urgent. By learning from other countries and adjusting it to the local legal system, such a court can bring more fairness, clarity, and faster decisions. It can also improve public trust and make health services better and safer.